The prevalence of workplace violence toward psychiatric nurses in Saudi Arabia and its effect on their quality of life - Sae’d M. Abu El-Kass; Sae’d M. Abu El-Kass; Sae’d M. Abu El-Kass; Osama Mahmoed Ellayan; Anas Muhmmad Turkman; Hind Mushabab Al Mansour; Musherh Alraied Alrowily; Khairyah Abdullah Alsobhan; Bushra Alraydh Alruwaili; Norah Saud Alqahtani; Hana Alraydh Alruwaili; Abdel Hamid El Bilbeisi (Frontiers in Psychiatry)
BackgroundWorkplace violence is a significant cause of work-related stress in nursing, affecting job performance and satisfaction and increasing burnout risk. This study aims to evaluate the prevalence of verbal and physical violence against psychiatric nurses and its impact on their quality of life.MethodsThis cross-sectional study was conducted from April to October 2024. A sample of 171 nurses was selected using a convenience sampling method. The study was carried out at Eradah Complex for Mental Health in Arar City, Eradah Hospital for Mental Health in Al Jouf City, and Mental Health Hospital in Al Qurayyat City. The authors evaluated workplace violence and quality of life among nurses using a questionnaire-based interview and a 36-item quality of life assessment tool. Statistical analysis was performed using SPSS version 25.ResultsThe participants’ mean age was 34.85 ± 4.74 years, 67.8% were male, and 52.7% had over 10 years of experience. The overall prevalence of workplace violence was found to be 100%, with 62% exposed to verbal violence and 38% to physical violence. Regarding quality of life, 66% had an average quality of life, 12.9% had a good quality of life, and 21.1% had a poor quality of life. Statistically significant associations were found between the type of violence and quality of life (P-value < 0.05).ConclusionThe study found significant levels of verbal and physical workplace violence among psychiatric nurses, with a significant correlation between violence and their quality of life. These results highlight the need for targeted interventions, including training programs, improved workplace safety policies, and continuous monitoring to support nurse well-being and job satisfaction.